Polymorpitisme of the red cells enzyme-systems in the population of Great Poland, taking sex into consideration - Przybylski, Zygmunt; Marcinkowski, Tadeusz (Anthropological Review, 1974)
The authors present data of the phenotypes and genotypes frequency concerning the systems of AP, ADA, AK and PGM.